Tradisi Rabo-Rabo: Sebuah Cerminan Ekspresi Identitas Komunitas Mardijkers di Kampung Tugu, Kelurahan Semper Barat, Jakarta Utara - Panjaitan, Michael Yoel; Suarsana, I Nyoman; Kaler, I Ketut (Sunari Penjor : Journal of Anthropology; Vol 8 No 1 (2024): Volume 8. No. 1. Maret 2024DO - 10.24843/SP.2024.v8.i01.p04, 2024)
Tugu community settlement are located in Semper Barat District, Jakarta Utara. Tugu community preserve the cultural expressions, specifically cultural activity that connects to Portuguese authentic tradition such as Rabo-Rabo. The uniqueness of the tradition are its existence lies beyond the plurality and modernity of Jakarta. Rabo-Rabo tradition are held occasionally when Christmas and new year celebration, the nuance of this tradition are corresponded with the Christianity and firmly grasp by Mardijkers strong kinship (social aspects), kerontjong music (art aspect), Christianity practices (religious aspects), and Mardijkers expressions (identity aspects). This research use Expressions of Religious Experience theory from Joachim Wach, and Functional Theory from Robert Merton. The Rabo-Rabo tradition is carried out for almost two weeks, starting from the Christmas prayer together until the key event of the year - bathing. The Rabo-Rabo tradition has the function of maintaining traditional culture, religious manifestations, and functions as social education for children.